Evaluation and Projection of Regional Climate over East Asia in CORDEX-East Asia Phase I Experiment - Kim, Gayoung; Cha, Dong-Hyun; Park, Changyong; Jin, Chun-Sil; Lee, Dong-Kyou; Suh, Myoung-Seok; Oh, Seok-Geun; Hong, Song-You; Ahn, Joong-Bae; Min, Seung-Ki; Kang, Hyun-Suk (Asia-Pacific journal of atmospheric sciences, 2021)
This study investigates the performance of simulated precipitation and estimates future changes in precipitation in CORDEX-East Asia Phase I. In the Historical experiment (1981–2005), a global climate model used as a lateral boundary condition does not realistically simulate the timing and intensity of the East Asian summer monsoon. Hence, it overestimates precipitation over East Asia. Generally, the results of the regional climate models also show similar bias characteristics to that of the large-scale forcing data. The individual biases of the regional climate model vary according to a model configuration, such as physical parameterization schemes. However, when bias correction is applied to data, the spatial variability and spatial correlation of the long-term mean precipitation become similar to the observations, and the annual cycle of precipitation is much improved. The two future experiments in the mid-twenty-first century period (2025–2049), show that mean and extreme precipitation amounts increase over the Korean Peninsula and northern China compared to the frequency of wet days. The increment of the low-level water vapor in all seasons can be attributed to the increased precipitation amounts; moreover, the East Asian summer monsoon is enhanced in mid-latitudes and lasts longer in summer owing to the strengthened western North Pacific Subtropical High. The increasing southerly wind from the East Asian summer monsoon over eastern China and the Korean Peninsula results in favorable conditions for the increase in precipitation.